2015
DOI: 10.5539/apr.v7n2p49
|View full text |Cite
|
Sign up to set email alerts
|

Simple Method for Phosphorus Diffusion on <100> Oriented P-Type Silicon Using New Phosphorus Gel as Dopant

Abstract: In this work, we try to make a p-type monocristalline silicon pn junction using an easier doping method. We combined spin-coating thin film deposition method and solid doping technique. This technique can be considered as variety of the SOD method.In this study, phosphorous-based gel compounds was prepared and deposited by spin coating. Heat treatment would thus, after deposition of thin layer, diffuse phosphorus atoms into the substrate to obtain a pn diode. Study by Secondary Ions Mass Spectrometry (SIMS) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…For example, in probe-assisted P-doping, it should be possible to indent through an overcoat layer of highly doped phosphosilicate glass (PSG) film to introduce P-dopants into the underlying substrate. 27,28 While we have previously shown that doping concentrations can be estimated from the measured CPD, 29 the focus of this paper is to demonstrate the concepts of probe assisted localized doping of Si substrates. Special cross-calibrated Al-doped samples would be needed to provide quantitative dopant concentrations for this PAD demonstration.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in probe-assisted P-doping, it should be possible to indent through an overcoat layer of highly doped phosphosilicate glass (PSG) film to introduce P-dopants into the underlying substrate. 27,28 While we have previously shown that doping concentrations can be estimated from the measured CPD, 29 the focus of this paper is to demonstrate the concepts of probe assisted localized doping of Si substrates. Special cross-calibrated Al-doped samples would be needed to provide quantitative dopant concentrations for this PAD demonstration.…”
Section: Introductionmentioning
confidence: 99%